The Significance of Leadership in the Evolution of Policy Styles: Reconciling Policy-Making in the Short and Long Term - Jale Tosun; Maria Tullia Galanti; Michael Howlett (Politische Vierteljahresschrift, 2022)
Can relatively short-term political leadership affect long-term national policy styles, and if so, how? We examine these questions in order to explain the temporal dynamics in national policy styles observed in several recent studies whose findings have challenged the traditional view that policy styles lend continuity and stability to policy-making. In its original formulation, the concept of policy styles refers to the extent to which governments are committed to anticipatory or reactive policy-making, as well as to whether they seek to reach consensus with societal groups over policies or simply impose decisions on them. Following these definitions, we contend that political leaders can alter a~long-held policy style and often do so due to strategic considerations, either in an attempt to improve their policy performance or in response to an exogenous shock, such as an economic crisis. We illustrate this argument by using longitudinal records of changes in country-level governance indicators which include data on dimensions of policy styles. Specifically we examine how two of the Sustainable Governance Indicators compiled by the Bertelsmann Foundation changed for Ireland, Italy, Malta, and Poland between 2014 and 2020. As the cases show, government leaders sought to alter long-standing processes and the arrangements of governance and policy-making. Our empirical findings support the overarching argument that the study of national policy styles should be combined with that of political leadership. – – Kann politische Führung, die über einen relativ kurzen Zeitraum ausgeübt wird, langlebige nationale Politikstile beeinflussen? Und wie würde sich dieser Einfluss darstellen? Die vorliegende Abhandlung untersucht diese Forschungsfragen, um eine Erklärung für die über die Zeit variierenden nationalen Politikstile anzubieten, die jüngere empirische Untersuchungen beobachtet haben. Diese Befunde stellen die traditionelle Sicht auf Politikstile als eine kontinuierliche und stabile Form der Politikgestaltung in Frage. Die ursprüngliche Konzeption von Politikstilen besagt, dass Regierungen im Rahmen der Politikgestaltung entweder Probleme antizipieren oder auf diese reagieren. Zudem würden manche Regierungen versuchen, bei der Politikgestaltung einen Konsens mit gesellschaftlichen Gruppen herzustellen, während andere die politischen Entscheidungen mit ihren entsprechenden Auswirkungen den gesellschaftlichen Akteuren auferlegen. Entsprechend dieser Definition erwarten wir, dass die politische Führung bestehende Politikstile aus strategischen Erwägungen heraus verändert, etwa um ihre Politikperformanz zu verbessern oder um auf einen externen Schock wie eine Wirtschaftskrise zu reagieren. Wir veranschaulichen unser Argument, indem wir Längsschnittdaten für Governance-Arrangements in verschiedenen Staaten verwenden, die unter anderem Politikstile abbilden. Genauer gesagt untersuchen wir, wie sich zwei der Sustainable Governance Indicators der Bertelsmann Stiftung zwischen 2014 und 2020 für Irland, Italien, Malta und Polen verändert haben. Die Fallanalysen zeigen auf, dass die jeweiligen Regierungen Einfluss auf bestehende Politikformulierungs- und Governance-Prozesse genommen haben. Die Befunde unterstützen somit unser Hauptargument, dass Untersuchungen zu nationalen Politikstilen die Rolle der politischen Führung mitberücksichtigen sollten.
Keywords: 320; Societal consultation; Stability; Strategic planning; Sustainable Governance Indicators; Governance; Gesellschaftliche Konsultation; Stabilität; Strategische Planung